From post-industrial to post modern society - Kumar, Krishan (Oxford Blackwell, 2005)
About the Book: From Post-Industrial to Post-Modern Society (Second Edition) "In the second edition of this classic study, Krishan Kumar introduces and assesses the rival claims of three theories crucial to an understanding of contemporary social theory: the information society; post-Fordism; and post-modernism. Explaining how these theories developed and why they have held such an appeal, the author provides the most readable and evenly balanced account of three very different, but overlapping paradigms. In a new andsubstantial introduction, Kumar places the three key approacheswithin the context of contemporary discourse on globalization. FromPost-Industrial to Post-Modern Society is essential reading foranyone seeking to understand contemporary theories of social, cultural, and economic change. " About the Author: Krishan Kumar "Krishan Kumar is William R. Kenan, Jr., Professor of Sociology at the University of Virginia. He was previously Professor of Social and Political Thought at the University of Kent, Canterbury. Since publishing the first edition of From Post-Industrial to Post-Modern Society (1995), he has co-edited Public and Private in Thought and Practice (1997) and Written 1989: Revolutionary Ideas and Ideals (2001) and The Making of English National Identity(2003). "
Keywords: Postmodernism-Social aspects